Serum Albumin Predicts Survival in Indian Adult Diffuse Large B cell Lymphoma Patients in the Rituximab Era - Gupta, Anshul; Mishra, Prabhakar; Nityanand, Soniya (Indian Journal of Medical and Paediatric Oncology, 2019)
Objective: The present study was done to evaluate the prognostic impact of the National Comprehensive Cancer Network-International Prognostic Index (NCCN-IPI) and serum albumin levels in the treatment outcome of Indian diffuse large B-cell lymphoma (DLBCL) patients in the rituximab era. Patients and Methods: We retrospectively analyzed the data (2013–2016) of 135 newly diagnosed DLBCL cases ≥18 years of age. All patients received Rituximab-Cyclophosphamide, Adriamycin, Vincristine, Prednisone (R-CHOP) chemotherapy. The analysis was carried out to assess the overall survival (OS) and progression-free survival (PFS) and the prognostic factors predicting the outcome. Results: Of the 135 patients in the study, 89 (65.9%) had B-symptoms, 20 (14.8%) had bulky disease, 79 (58.5%) had advanced disease (Stage III and IV), and 29 (21.5%) had primary extranodal involvement. Serum albumin ≤3.5 g% was present in 71 (52.6%) patients. About 74 (54.8%) cases were risk stratified to NCCN-IPI high-intermediate-risk group, while 18 (13.3%) patients were categorized into high-risk group. The median PFS and OS of our study cohort were 19 months (95% confidence interval [CI] = 2.59–35.4) and 38 months (95% CI = 9.02–55.68), respectively. Serum albumin ≤3.5 g/dl was significantly associated with poor OS (hazard ratio [HR] = 3.99, 95% CI = 2.25–7.07, P < 0.001) and PFS (HR = 3.71, 95% CI = 2.20–6.26, P < 0.002). Similarly, low NCCN-IPI (<4) was significantly associated with improved OS (HR = 0.21, 95% CI = 0.09–0.47, P < 0.005) and PFS (HR = 0.19, 95% CI = 0.09–0.41, P < 0.001), respectively. These two factors (serum albumin and NCCN-IPI) retained their prognostic significance with respect to OS and PFS in the multivariate analysis. Conclusion: The NCCN-IPI prognostic model and serum albumin levels have independent prognostic significance in Indian DLBCL patients. Serum albumin is a readily available, easy to standardize, and cheap investigation requiring no specialized expertise and holds promise for being incorporated in future DLBCL prognostic risk models.
Keywords: Albumin; diffuse large B-cell lymphoma; National Comprehensive Cancer Network-International Prognostic Index; prognosis